Analysis of Sociodemographic Factors and Perception of Side Effects Based on Differences in Covid-19 Risk Factors in Pati District - Desyana Indira Putri; Budiyono; Ayun Sriatmi (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: The COVID-19 pandemic has had a significant impact on public health, including in Pati District. Sociodemographic factors such as age, gender, education, employment, and economic status, as well as perceptions of vaccination side effects play an important role in determining the level of COVID-19 risk. An in-depth understanding of these different risk factors is essential to formulate effective and targeted mitigation strategies. Objective: This study aims to analyze how sociodemographic factors (age, gender, education, employment and marital status) and perceptions of vaccination side effects contribute to differences in COVID-19 risk factors in Pati District. Method: The type of research used in this study is quantitative research with a cross sectional approach. The sample size was 210 respondents. The instrument used was a questionnaire with an interview method. Data were analyzed using the Mann Whitney test for numerical data (knowledge and perception of side effects) and using the Chi-Square test for categorical data (age, gender, education, occupation and marital status). Result: The results of the relationship test show that the p value <0.05 between gender and perception of side effects on COVID-19 risk factors Conclusion: Sociodemographic factors and perceived side effects of vaccination play an important role in determining the level of COVID-19 risk in Pati District. Better education on the safety and benefits of vaccination and approaches tailored to sociodemographic characteristics can help reduce risk and increase vaccination participation in the community.